The durability of seawater sea-sand concrete beams reinforced with metal bars or non-metal bars in the ocean environment. Issue 2 (January 2020) - Dong, Zhiqiang; Wu, Gang; Zhao, Xiao-Ling; Zhu, Hong; Lian, Jin-Long
In this article, the flexural durability of three types of seawater sea-sand concrete beams that were fully reinforced with steel bars, 304 stainless steel bars, or fiber-reinforced polymer bars were comparatively tested. Beam specimens were conditioned in a 40°C seawater wet–dry cycling environment and a 50°C seawater immersion environment for up to 9 months with an interval of 3 months. The test results showed that in the absence of an additional current (even if the temperature is elevated), the flexural properties of the seawater sea-sand concrete beams reinforced with steel bars and stainless steel bars after 9 months of conditioning did not show any degradation trends. However, for the carbon fiber–reinforced polymer bar–reinforced beams (top bars and stirrups are both basalt fiber–reinforced polymer bars) conditioned in the high-temperature and high-humidity environment considered, the failure modes changed from concrete crushing in the pure bending section to concrete crushing at loading points in the shear span with a maximum reduction of 30% in the ultimate load-carrying capacity. In addition, the crack distribution of conditioned carbon fiber–reinforced polymer bar–reinforced beams became sparse, and the crack width increased significantly, with a maximum of 2.2 times. In addition, obvious sudden load drops were observed in the tested load–displacement curves.